การจัดพอร์ตการลงทุนที่มีประสิทธิภาพที่ไม่มีการยืมขายด้วยตัวแบบดัชนีเดียว - สิตานันท์ นิยมสมาน (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
In this project, we prove the efficient portfolio management with no short selling theorem using index models. For an investment in n assets. In addition, we apply the theorem to determine the efficient portfolio with no short selling for a stock investment on stock exchange.